1947
DOI: 10.1017/s0022143000001088
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion Flow in Glaciers: A description of tests to prove the hypothesis and some details regarding its influence on glacial erosion

Abstract: IN the middle of last century, Agassiz, Tyndall and others showed that a glacier flowed faster at its centre than at its margin. Partly from experiments and partly from the assumption that it behaved like a river, it became generally accepted that it also flowed faster at the surface than lower down. This belief was held until ten or fifteen years ago although search through earlier literature shows that evidence was accumulating which might disprove this. During the thirtit;s of this century several writers b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1947
1947
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…This belief was held until ten or fifteen years ago although search through earlier literature shows that evidence was accumulating which might disprove this. (Seligman, 1947 )…”
Section: Early Undercurrentsmentioning
confidence: 99%
See 4 more Smart Citations
“…This belief was held until ten or fifteen years ago although search through earlier literature shows that evidence was accumulating which might disprove this. (Seligman, 1947 )…”
Section: Early Undercurrentsmentioning
confidence: 99%
“…For example, Gerald Seligman apparently was drawn to these ideas. In assessing the pros and cons of the extrusion flow theory, Seligman (1947) suggested that Holmes’s work supported the idea that…”
Section: Early Undercurrentsmentioning
confidence: 99%
See 3 more Smart Citations